SWOT Analysis in Quality Improvement Graduate Competency Standards in Elementary School - Imas Damayanti Lovita; Arinda Nurpratiwi; Mimin Mimin (Indonesian Journal of Primary Education, 2022)
The purpose of this research to describe the implementation of the Graduate Competency Standards (SKL), the SWOT analysis of the SKL implementation, and to propose an action plan. action plans in different elementary schools. This study applied a qualitative descriptive approach and data triangulation model to include orientation, exploration and investigation phases. The 123 study participants were school principals, classroom teachers, subject teachers, education staff, school committees, and parents. Most of the quality indicators have been implemented and developed in primary schools, according to the results. Students are unfamiliar with writing and do not participate in school curriculum committees, both unconsolidated indicators of quality. The school's vision and aim are already aligned with the SKL, and all teachers hold at least an S1 certificate. Teacher IT skills are still insufficient, and some teachers lack formal educational degrees, which are problems. In terms of possibilities, the school, school committee, teachers, and student parents have created a close bond, with most school programs Obtaining full parental support. Meanwhile, external competition, particularly from private schools that do not yet have an alumni forum, poses a challenge. The bulk of the SKL quality indicators has been implemented and developed in elementary schools, according to the study's results. Internal (strengths and weaknesses) and external (opportunities and threats) factors, as well as an action plan, are unique to each institution (action plan). In certain primary schools, SKL offers a variety of activities, schedules, and objectives.